2015
DOI: 10.1055/s-0034-1379893
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Photochemical Mechanisms for Cyclobutane Formation in Bielschowskysin Biosynthesis

Abstract: The unique structure of furanocembranoid natural product bielschowskysin has provoked a number of biosynthetic hypotheses: quantum chemical calculations provide a means to assess the feasibility of postulated mechanisms in the construction of this unusual carbon skeleton. Calculations reveal that thermal closure is possible in water via an unusual concerted cyclobutane-forming transition state without the intervention of an enzyme. Photocycloaddition is computed to be extremely efficient, provided enol ether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…3a Alongside the total syntheses and synthetic attempts towards these polycyclic natural furanocembrane derivatives, computational studies have been carried out to understand the reliability of these proposed biomimetic connections. 3b c , 12 13 14 Quantum chemical calculations agree well with the experimental observations. This account illustrates how biomimetic syntheses of natural products guided by computational chemistry can be a useful approach for synthetic chemists to better understand the pathways that they develop for biomimetic synthesis.…”
Section: Introduction To Polycyclic Furanocembrane Derivativessupporting
confidence: 71%
See 1 more Smart Citation
“…3a Alongside the total syntheses and synthetic attempts towards these polycyclic natural furanocembrane derivatives, computational studies have been carried out to understand the reliability of these proposed biomimetic connections. 3b c , 12 13 14 Quantum chemical calculations agree well with the experimental observations. This account illustrates how biomimetic syntheses of natural products guided by computational chemistry can be a useful approach for synthetic chemists to better understand the pathways that they develop for biomimetic synthesis.…”
Section: Introduction To Polycyclic Furanocembrane Derivativessupporting
confidence: 71%
“…To assess the feasibility of photochemical and nonphotochemical pathways to bielschowskysin ( 10 ), Tang et al carried out quantum chemical calculations to investigate the potential mechanisms involved in formation of the strained cyclobutane in the biosynthesis of bielschowskysin. 3b With the optimized geometry of the enol ether 16 and bielschowskysin ( 10 ), Tang et al located the key transition state TS 16,10 connecting the reactant and the product and computed the activation free energy for this transformation as 21.6 kcal mol –1 at the CPCM(water)-ωB97XD/def2-TZVPP level, as illustrated in Scheme 7a . Tang et al studied the potential energy surface and the relative energy for the formation of the C7–C11 and C6–C12 bonds.…”
Section: Computational Studies On the Biomimetic Synthesis Of Bielsch...mentioning
confidence: 99%
“…Theoretically, Paton et al explored the thermal-and photoinduced cycloaddition reaction of cyclobutane formation in bielschowskysin product in the gas phase by DFT calculations, indicating that the PD pathway is more favorable than the thermal pathway. 26 You et al reported that indole derivatives with alkene group form cyclobutane through the intramolecular PD reaction, in which the alkene is excited to its first triplet state (T 1 ) via the energy transfer mechanism. 27 Glorius et al investigated the intermolecular PD reaction mechanism of coumarins, in which the intersystem crossing (ISC) process of the triplet diradical species allows the subsequent C-C bond formation as the diastereoselectivity determining step to finally deliver the cycloaddition product.…”
Section: Introductionmentioning
confidence: 99%